FACTORS SUPPORTING AND HINDERING THE USE OF ENGLISH AT INTERNATIONAL CLASS PROGRAM (ICP) FACULTY OF TARBIYAH, UIN MAULANA MALIK IBRAHIM MALANG - Djoko Susanto (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2014)
This study investigates factors supporting and hindering the implementation or the use of English by the students of International Class Program (ICP) Faculty of Tarbiyah, UIN Maulana Malik Ibrahim Malang. The primary purpose of this study is to provide recommendations for the Faculty especially the program coor-dinator to acknowledge the problems that need to be solved. This study involved a number of students joining the program. To obtain the data, interviews and questionnaires were distributed to 30 students. After analyz-ing the data, factors supporting and hindering the use of English at ICP were identified. Factors supporting the program are: (1) the students’ motivation, (2) the role of lecturers, and (3) the instructional materials. However, some factors hindering the program include: (1) not all students had an electronic English diction-ary, (2) both the lecturers and the students were inconsistent to use English, (3) the poor students’ English mastery sometimes also hindered the teaching process, (4) there was no language forums held in English, (5) there was no language lab, (6) the students had not been aware of the importance of practicing English, (7) the ICP students claimed that most of the materials they learned were written in Indonesian. The program coordinator acknowledges the students’ interest in learning English. As has been stated before, most of the students have high motivation to learn English. Thus, the program coordinator (1) should notice this and be very sensitive with this situation, because the students’ motivation is a very important thing in gaining more English development, needs to give extended role to the lecturers. They are required not only teaching the content materials but also some aspects of English entities, (3) needs to explain clearly that both lecturers and students need to make an agreement regarding the consistency of using English. Key words: factors supporting, factors hindering, International Class Program (ICP)